Follicle stimulating hormone receptor gene polymorphism and its association with fecundity in goats - SHINDE, GAYATRI; INGAWALE, MAHESHKUMAR; KURALKAR, SHAILENDRA; BANKAR, PRAVIN; ALI, SAJID; HAJARE, SUNIL; INGOLE, RANJIT (The Indian Journal of Animal Sciences, 2019)
Pluriparous goats (73) in between second to fifth parity with history of breeding 30 days before were selected for present study. A real time B-mode ultrasonography machine equipped with a linear array 7.5 MHz transrectal scanner was used for diagnosis of early pregnancy and twinning in goats. Out of 73 goats, 40 were detected pregnant with 22 goats with single embryo and 18 goats with twin embryos. Genomic DNA was extracted from the blood of all pregnant goats and polymerase chain reaction (PCR) with FSHR gene specific primers was carried out. The PCR product for FSHR gene was digested by restriction enzyme MSCI. Two genotypes AA and AB having amplification size (214 bp, 90 bp) and (214 bp, 90 bp and 304 bp) were detected, respectively. In AA genotype, 21 single and 9 twins were observed while 1 single and 9 twin embryos were observed in AB genotype. The percentage of single and twins was 70% and 30% in AA genotype, and 10% and 90% in AB genotype. In AA genotype, the average litter size was 1.3 while in AB genotype it was 1.9 and the difference was statistially significant. The AB genotype for the FSHR gene is responsible for more twining percentage.